Kinetic and structural aspects of tantalum hydride formation - Simonović B.R.; Mentus Slavko V.; Dimitrijević Radovan Ž. (Journal of the Serbian Chemical Society, 2003)
Tantalum hydrides of various composition were synthesized by equilibrating tantalum with hydrogen at six different temperatures from 573 to 823 K under a constant hydrogen pressure of 1 bar. Both the exact Ta/H mole ratios and the kinetic parameters of hydriding were determined on the basis of the dependence of the H/Ta mole ratio on time. The influence of stoichiometry on the appearance of X-ray powder diffractograms at room temperature was studied. As a consequence of hydriding, for ratios H/Ta > 0.2, the original bcc Ta-lattice undergoes distortion, manifesting itself as both a shift and a splitting of the X-ray patterns in the X-ray diffractograms. For samples with H/Ta < 0.2, the appearance of some superstructure reflections at low Bragg angles was noted, which suggests a long range ordering of hydrogen with orthorhombic symmetry.